Enhancing Students’ Creativity through STEM Project-Based Learning - Sofi Hanif; Agus Fany Chandra Wijaya; Nanang Winarno (Universitas Pendidikan Indonesia, 2019)
In some school, teacher-centered is commonly found in the learning process. The learning process itself is still in the form of direct transfer of knowledge from teacher to students. Actually, students will learn better if they are engaged in meaningful learning activity. STEM project-based learning is one of alternative teaching strategies that engaged students in meaningful learning. The aim of this study is to investigate the impact of STEM project-based learning on students' creativity in the topics of light and optics. The study used qualitative research with narrative design. Data collection technique that used is observation. The population is eight grade students in one of Junior Secondary School that is located in Bandung, Indonesia. The sample consist of 25 students that chosen based on purposive sampling technique. The data is obtained through Creativity Product Analysis Matrix (CPAM). There are three creativity dimension that used in this study which are resolution, elaboration and novelty dimension. Students’ creativity is obtained as much 76% which categorized as good. Based on the result, STEM project-based learning give the good impact on students' creativity. STEM project-based learning can be used as alternative teaching strategies in Junior Secondary School.